Multimodal imaging markers of tau, neuroinflammation and atrophy to predict clinical progression in progressive supranuclear palsy: Neuroimaging: Other neurodegenerative disorders. (7th December 2020) - Malpetti, Maura; Passamonti, Luca; Jones, P Simon; Rittman, Timothy; Fryer, Tim D; Hong, Young T; Street, Duncan; Rodríguez, Patricia Vázquez; Bevan‐Jones, W Richard; Aigbirhio, Franklin I; O'Brien, John T; Rowe, James B
Abstract: Background: Progressive Supranuclear Palsy (PSP) is associated with tau pathology and neurodegeneration, particularly in basal ganglia, diencephalon, and brainstem. Recently, neuroinflammation has been recognized as another key aspect in the pathophysiology of PSP. Understanding whether these three pathological features predict the clinical progression is crucial to develop new prognostic measures. Here, we studied how baseline assessments of in vivo tau pathology (measured by [18F]AV‐1451 PET), neuroinflammation ([11C]PK11195 PET), and atrophy (structural MRI) predicted longitudinal clinical changes in n=17 patients with PSP‐Richardson's syndrome. Method: All patients underwent a baseline multi‐modal assessment with [18F]AV‐1451 PET, [11C]PK11195 PET, and structural MRI. They were clinically assessed up to 4 years, with the PSP rating scale. Regional PET binding potentials and grey‐matter volumes across all brain regions were summarised by method‐specific Principal Component Analyses (PCAs). A linear mixed model was applied to the longitudinal PSP rating scale scores to estimate the rate of annual decline in each participant. We regressed the individuals' estimated rate of clinical progression on neuroimaging components, to identify the prognostic value of PET and MRI markers in different clusters of regions, with age and time between scan and the first clinical assessment as covariates. Result: PCAs identified four components for each ligand, reflecting the relative expression of tau pathology or neuroinflammation in distinct groups of brain regions, and seven components of grey‐matter volumes. Patients showed an average increase of 6.15 points (p<0.0001) per year on the PSP rating scale. PCA‐derived components reflecting tau burden (r=0.639, p=0.010) and neuroinflammation (r=0.596, p=0.019) in PSP‐related subcortical areas were linked to the annual rate of change of disease severity. These pathology markers components were associated with atrophy of the same regions (tau: r=‐0.626, p=0.007; neuroinflammation: r=‐0.584, p=0.014) but atrophy did not correlate with clinical progression (r=‐0.474, p=0.074). Conclusion: In vivo PET markers of both tau pathology and neuroinflammation in subcortical regions predicted clinical progression in PSP patients. Our results encourage the application of [18F]AV‐1451 and [11C]PK11195 PET in PSP as stratification measures that inform prognosis, to develop new targeting disease‐modifying therapies and empower clinical trials.